Analysis of mitochondrial DNA sequences in childhood encephalomyopathies reveals new disease-associated variants - Wani, Aijaz A.; Ahanger, Sajad H.; Bapat, Sharmila A.; Rangrez, Ashraf Y.; Hingankar, Nitin; Suresh, C. G.; Barnabas, Shama; Patole, Milind S.; Shouche, Yogesh S. (Plos One, 2007)
Background. Mitochondrial encephalomyopathies are a heterogeneous group of clinical disorders generally caused due to mutations in either mitochondrial DNA (mtDNA) or nuclear genes encoding oxidative phosphorylation (OXPHOS). We analyzed the mtDNA sequences from a group of 23 pediatric patients with clinical and morphological features of mitochondrial encephalopathies and tried to establish a relationship of identified variants with the disease. Methodology/Principle Findings. Complete mitochondrial genomes were amplified by PCR and sequenced by automated DNA sequencing. Sequencing data was analyzed by SeqScape software and also confirmed by BLASTn program. Nucleotide sequences were compared with the revised Cambridge reference sequence (CRS) and sequences present in mitochondrial databases. The data obtained shows that a number of known and novel mtDNA variants were associated with the disease. Most of the non-synonymous variants were heteroplasmic (A4136G, A9194G and T11916A) suggesting their possibility of being pathogenic in nature. Some of the missense variants although homoplasmic were showing changes in highly conserved amino acids (T3394C, T3866C, and G9804A) and were previously identified with diseased conditions. Similarly, two other variants found in tRNA genes (G5783A and C8309T) could alter the secondary structure of Cys-tRNA and Lys-tRNA. Most of the variants occurred in single cases; however, a few occurred in more than one case (e. g. G5783A and A10149T). Conclusions and Significance. The mtDNA variants identified in this study could be the possible cause of mitochondrial encephalomyopathies with childhood onset in the patient group. Our study further strengthens the pathogenic score of known variants previously reported as provisionally pathogenic in mitochondrial diseases. The novel variants found in the present study can be potential candidates for further investigations to establish the relationship between their incidence and role in expressing the disease phenotype. This study will be useful in genetic diagnosis and counseling of mitochondrial diseases in India as well as worldwide.

Analysis of reactive oxygen species and antioxidant defenses in complex I deficient patients revealed a specific increase in superoxide dismutase activity - Wani, Aijaz A.; Rangrez, Ashraf Y.; Kumar, Himanshu; Bapat, Sharmila A.; Suresh, C. G.; Barnabas, Shama; Patole, Milind S.; Shouche, Yogesh (Free Radical Research, 2008)
The mechanism of free radical production by complex I deficiency is ill-defined, although it is of significant contemporary interest. This study studied the ROS production and antioxidant defenses in children with mitochondrial NADH dehydrogenase deficiency. ROS production has remained significantly elevated in patients compared to controls. The expression of all antioxidant enzymes significantly increased at mRNA level. However, the enzyme activities did not correlate with high mRNA or protein expression. Only the activity of superoxide dismutase (SOD) was found to correlate with higher mRNA expression in patient derived cell lines. The activities of the enzymes such as glutathione peroxidase (GPx), Catalase (CAT) and glutathione-S-transferase (GST) were significantly reduced in patients (p < 0.05 or p < 0.01). Glutathione reductase (GR) activity and intracellular glutathione (GSH) levels were not changed. Decreased enzyme activities could be due to post-translational or oxidative modification of ROS scavenging enzymes. The information on the status of ROS and marking the alteration of ROS scavenging enzymes in peripheral lymphocytes or lymphoblast cell lines will provide a better way to design antioxidant therapies for such disorders.
Keywords: antioxidant enzymes; mitochondrial complex I; mitochondrial myopathies; Reactive Oxygen Species (ROS)